Genomic and structural analysis of the endocannabinoid system in Moroccans: A novel CNR1 variant (V392A) impairs CB1 receptor stability - Hanane Abbou; Rihab Festali; Mohammed Walid Chemao-Elfihri; Mohammed Hakmi; Souad Kartti; Saber Boutayeb; Lahcen Belyamani; Rachid Eljaoudi (PLoS ONE, 2026)
The Endocannabinoid System (ECS) is vital for human physiology, and genetic variation within its components can alter function and therapeutic responses. The genetically diverse Moroccan population offers a unique opportunity for pharmacogenomic insight. This study performs a comprehensive genomic analysis of 11 core ECS genes in 109 Moroccan individuals, identifying 170 novel variants. We then performed a deep in silico functional characterization of a novel, high-confidence CNR1 variant (V392A). Extensive, triplicate 500 ns molecular dynamics (MD) simulations were conducted on both the wild-type (WT) and mutant (MT) CB1 receptor. The simulations revealed that the V392A mutation induces significant structural destabilization, evidenced by increased RMSD/RMSF, a consistent loss of α-helicity, and altered interhelical distances crucial for G-protein coupling. Free Energy Landscape (FEL) analysis confirmed the mutant receptor occupies a broader, higher-energy conformational state. This “genomics-to-function” pipeline demonstrates that the Moroccan population harbors significant novel ECS genetic diversity and that the unique V392A CNR1 variant impairs CB1 receptor stability, suggesting a potential for altered signaling and pharmacological responses.